2008
DOI: 10.1016/j.cell.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of Nucleosome Positioning in the Human Genome

Abstract: The positioning of nucleosomes with respect to DNA plays an important role in regulating transcription. However, nucleosome mapping has been performed for only limited genomic regions in humans. We have generated genome-wide maps of nucleosome positions in both resting and activated human CD4+ T cells by direct sequencing of nucleosome ends using the Solexa high-throughput sequencing technique. We find that nucleosome phasing relative to the transcription start sites is directly correlated to RNA polymerase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

99
1,317
8
21

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,252 publications
(1,457 citation statements)
references
References 67 publications
99
1,317
8
21
Order By: Relevance
“…This is largely due to the requirement for chromatin to be reorganized to create access to key differentiation loci. The opening of chromatin is aided by the recruitment of histone acetyl transferases (HATs), chromatin remodelling enzymes and histone methyltransferases (HMTs), as well as the recently discovered histone lysine demethylases (KDMs) and ten-eleven translocation (TET; also known as methylcytosine dioxygenase) proteins that initiate DNA demethylation [130][131][132][133][134][135][136] (FIG. 5b).…”
Section: Dna Accessibility By Modification Of Dna and Histonesmentioning
confidence: 99%
“…This is largely due to the requirement for chromatin to be reorganized to create access to key differentiation loci. The opening of chromatin is aided by the recruitment of histone acetyl transferases (HATs), chromatin remodelling enzymes and histone methyltransferases (HMTs), as well as the recently discovered histone lysine demethylases (KDMs) and ten-eleven translocation (TET; also known as methylcytosine dioxygenase) proteins that initiate DNA demethylation [130][131][132][133][134][135][136] (FIG. 5b).…”
Section: Dna Accessibility By Modification Of Dna and Histonesmentioning
confidence: 99%
“…NFRs have been mapped across genomes by mapping the nucleosome occupancy at high resolution. [27][28][29][30] Computational and experimental approaches can largely reconstitute patterns that are observed in cells, suggesting information encoded in the DNA itself plays a major role in directing nucleosome placement. Complete reconstitution of observed nucleosomal patterns is generally attributed to transcription factor-dependent recruitment of nucleosome remodeling complexes.…”
Section: Divergent Transcription In Yeastmentioning
confidence: 99%
“…It has been reported that nucleosomes acquire an open chromatin structure following the binding of transcription factors ). To analyze the nucleosome structure, Nucleosome-Seq (Albert et al 2007;Jiang and Pugh 2009;Schones et al 2008) was used in DLD-1 and TIG-3 cells. We generated a total of 130,088,634 36-bp sequence tags from micrococcal nuclease-digested genomic DNA and calculated the occupancy of the nucleosome according to a previously reported procedure (Albert et al 2007) (Supplementary Fig.…”
Section: Epigenetic Regulation In Regions Surrounding Hif-1a Binding mentioning
confidence: 99%
“…Furthermore, we carried out Illumina GA sequencing analysis using micrococcal nuclease-digested genomic DNA (Nucleosome-Seq) (Albert et al 2007;Jiang and Pugh 2009;Schones et al 2008). We examined the changes in nucleosome structure caused by HIF-1a binding and the subsequent transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%